PENERAPAN PROCESS APPROACH UNTUK MENINGKATKAN KEMAMPUAN PENGEMBANGAN THESIS STATEMENT PADA MAHASISWA PRODI BAHASA INGGRIS DALAM MATA KULIAH WRITING III - Rumiri Rotua Aruan (BAHAS, 2010)
The aim of this classroom action research was to investigate the effectiveness of process approach in increasing students’ essay writing ability. The writer found in her classes that the students didn’t know how to develop the topic when they asked to write an essay. The subjects of this research were the students of English Study program who took writing III. Before the treatment was conducted, the subjects were given pre-test and after ten times treatment, post-test was held. Four steps were conducted to this research: planning, action, reflection, and revision/evaluation. The result showed the mean score of pre-test was 54.02 and the post-test was 79.2. In other words, this research proved that process approach can be one of the alternatives way in teaching essay writing.   Key words:  process approach, thesis statement